Amylase Producing Bacillus megaterium T04 Isolated in Rach Lang Stream of Vietnam - Nguyen Tu, Doan Vinh, Le Thu (Journal of Applied Pharmaceutical Science, 2015)
In the study, Bacillus megaterium T04 isolated from Rach Lang stream in Vietnam was identified. The stream samples were diluted in 0.9 % NaCl broth and then spread onto the ISP4 supplemented with rice and wheat starch. The colonies showed the strongest hydrolyzing activity were picked up and identified by biochemical test and 16S rRNA sequencing analysis. The starch hydrolyzing ability of this strain was detected by starch agar plate method. For maximum α-Amylase production, including 174.7 IU/ml and 0.2 IU/ml in medium containing wheat and rice, respectively was obtained after 72 h of incubation. The enzyme still showed high activity in 60% ammonium sulfate that was necessary for study on the enzyme characteristics. As a result, Bacillus megaterium T04 could produce high yield of amylase in simple conditions.
Keywords: Bacillus megaterium T04, Rach Lang stream, starch hydrolyzing ability, wheat starch, rice starch.